(untitled) (Modern education and development, 2025)
The article presents the possibilities of intelligent data analysis, automatic data analysis, and extraction of useful knowledge from data, due to the fact that the amount of data generated around the world is very large and frequently updated, and the need to use advanced technologies such as artificial intelligence and machine learning in data collection and analysis.